Research on explosive damage effects of tungsten fiber-reinforced Zr-based bulk metallic glass matrix composite shell - Xing, Bingnan; Du, Chengxin; Du, Zhonghua; Fu, Huameng; Zhu, Zhengwang; Zhou, Feng (Frontiers in Materials, 2023)
To expand the application range of explosive fragmentation projectiles, tungsten fiber-reinforced bulk metallic glass matrix composite (WF/Zr-MG) is used as the warhead shell in static explosion experiments, and is compared with 40CrMnSiB steel shells. The experimental results showed that, compared with 40CrMnSiB steel shells, the fragments produced by the WF/Zr-MG shell exhibit a larger aspect ratio, smaller average size, and a greater number of fragments at distances of 3 m and 5 m, with an equal number of fragments at a distance of 8 m. Theoretical calculations showed that the initial velocity of the fragments produced by the WF/Zr-MG shell is lower, but their velocity decay is slower, resulting in a greater determined damage range. The research results showed that WF/Zr-MG can be used as a shell material for explosive fragmentation projectiles, which can enhance their destructive power.